The foolish wisdom of humans versus the wise wisdom of God in the book of Isaiah - Chris van der Walt (In die Skriflig, 2024)
When wisdom in the book of Isaiah is investigated, there is a deviation from the normal sense of understanding wisdom as a particular mental ability. What is out of the ordinary about the use of wisdom in the book of Isaiah is that it is used more often for clearly unwise people than for the wisdom of God. In ten texts, mainly from Isaiah 1−39, the ‘wisdom’ of the unwise is juxtaposed with the wisdom of God. In these texts, all the dominant powers in the Ancient Near East are addressed. In this manner, facets of God’s wisdom are brought to the fore, which is not evident in the semantic meaning of the חָכָם word group, where wisdom typically carries the idea of normativity, or good character and virtue (Pr 1:1–7). Therefore, the focus of this article will be to show how the actions of Yahweh toward both his people and his adversaries portray his wisdom, with a clear indication of what his wisdom entails in the book of Isaiah. This study calls for the re-evaluation of wisdom, advocating for a theocentric understanding that aligns with Yahweh’s will expressed in covenantal fidelity.